The animated pocket dictionary of orthopedics ([Singapore] : Focus Medica, 2011)
The FOCUS Animated Pocket Dictionary of Orthopedics, the first ever animated dictionary in the subject, fills that void quite effectively. A must-have resource for physicians and students who would greatly benefit from this module, it covers orthopedics related terms and definitions. All the definitions have been described with breathtaking, state of the art 3D animations.
A-V.
Keywords: Orthopedics; Orthopedics; Dictionary; Electronic books; Dictionaries